2017
DOI: 10.1016/j.actamat.2017.03.079
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution and superelastic behavior in Ti-35Nb-2Ta-3Zr alloy processed by friction stir processing

Abstract: This work investigates systematically the phase transformation and superelasticity in TiNbTaZr alloy prepared by friction stir processing (FSP). Multiple-pass FSP with a 100% accumulated overlap to three passes was implemented. The influence of the processing parameters on the microstructural evolution and superelasticity in stir zone, transition zone, and heat affected zone were investigated. After recrystallization, existing dislocations gradually accommodate themselves at sub-grain boundaries. Increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(67 citation statements)
references
References 65 publications
(110 reference statements)
0
67
0
Order By: Relevance
“…Titanium alloys have many advantages, including lower Young's moduli, greater corrosion resistance, higher strength, and lighter weight compared with 316LSS and Co–Cr alloys . Their applications range from aerospace crafts to medical implants.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium alloys have many advantages, including lower Young's moduli, greater corrosion resistance, higher strength, and lighter weight compared with 316LSS and Co–Cr alloys . Their applications range from aerospace crafts to medical implants.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the ultrafine‐grained materials are expected to be the next generation of biomedical materials. So far, many different severe plastic deformation (SPD) methods have been proposed, including equal channel angular extrusion (ECAP) and accumulative roll bonding (ARB), high‐pressure torsion (HPT), multi‐directional forging, twist extrusion, cyclic‐extrusion–compression, friction stir processing (FSP) …”
Section: New Preparation Methods Of Ti Alloys For Biomedical Applicatmentioning
confidence: 99%
“…Although Ti alloy has high specific strength and high corrosion resistance, their wear resistance is not desirable . Surface modification techniques including physical deposition methods (such as ion implantation, laser cladding, physical vapor deposition, and plasma spray coating), thermochemical surface treatments (such as nitriding, carburization, oxygen diffusion hardening, and boriding), and surface severe plastic deformation (such as friction stir processing and surface mechanical attrition treatment) have been employed to improve the surface properties of Ti alloys. TiN and diamond‐like carbon (DLC) coatings are commonly used in both physical deposition methods and thermochemical surface treatments.…”
Section: Surface Modification Of Ti Alloys For Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Friction stir welding (FSW), a solid-state joining technique, was originally invented to weld Al alloys [6], and recently applied into Ti alloys due to its advantages over fusion welding [7][8][9][10][11][12][13]. It was reported that the efficiency of FSW Ti alloy joints could be over 90% [14].…”
Section: Introductionmentioning
confidence: 99%